A kormányzó utódlásának kérdése a Horthy-korszakban - Olasz, Lajos (Közép-Európai Közlemények, 2015)
The Treaty of Trianon prohibited the return of either Charles IV or any other member of the Habsburg family to the Hungarian throne. However, the Hungarian political forces hoped that the „king” question would be solved soon. By the 1930-ies, however, it became clear that for the time being it was impossible to occupy the throne, consequently, the institution of regency would last for a longer period. That was why regent succession needed to be regulated. Miklós Horthy wanted to have a determinant voice in his successor’s denomination. But the parliament wanted to keep this right to itself. Finally, in 1937, a compromise was reached. The regent was able to propose 3 people as successor, while the parliament had the right either to choose from them or nominate a 4th prospect. At the beginning of the 1940-ies, as a result of the war situation, it became inevitable to regulate even the substitution of the regent. That was why in February 1942, upon Horthy’s request, the parliament elected a vice regent. The new post was allocated to István Horthy (elder son of the regent). The vice regent, however, did not have the right of succession. He could only function as the head of state temporarily, until the parliament elected a new regent.